Regulatory framework on cryptocurrency in European Union and Republic of Latvia: AML/CFT, tax evasion - Bindule, Laura (Riga Graduate School of Law, 2018)
Cryptocurrencies have gained popularity among the investors, merchants and companies, this resulted in the close paid attention from that state authority’s side. Some governments have responded to the growing alternative payment method. However, up to this date, there is no exact distinction on how the new financial instrument has to be addressed. This research focused only on the European Union and Republic of Latvia legislative framework and initiatives on regulatory towards cryptocurrencies on preventing money laundering, terrorist financing, and tax fraud and evasion.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Cryptocurrency